Systematic Cognition and Path Optimization of Comprehensive Utilization of Abandoned Mines —— Based on the Theoretical Perspective of Factor Endowment Differences - Jialong WU; Hongju LI; Kai WANG; Shaoqing SU; Yan JIANG; Yun LUO; Yang YU (Kuangchan zonghe liyong)
Comprehensive utilization of abandoned mines is an important issue to improve resource utilization and promote high-quality development. By systematically recognizing the composition, endowment and driving mechanism of comprehensive utilization of mines, it provides theoretical basis and research ideas for promoting the optimization and improvement of comprehensive utilization of abandoned mines. This paper adopted the method of literature review, induction and deduction, combs the evolution, policy and connotation of comprehensive utilization of mines in China, and explained the driving mechanism and action mechanism of comprehensive utilization of mines in combination with empirical examples at home and abroad. The factors of comprehensive utilization of abandoned mines and their endowment differences were analyzed. The business logic and key technical links of comprehensive utilization of mines were sorted out, and the optimization path of comprehensive utilization of mines based on "type division - problem identification - potential evaluation - operation mechanism design - policy innovation" was proposed.